2000
DOI: 10.1159/000057509
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Engineering Controls for Airborne Lead Exposure during Renovation/Demolition of a Commercial Building

Abstract: Airborne lead exposure was evaluated during renovation/demolition of a building that contained lead-based paint (LBP). During this work, different engineering and work practice controls were utilized for prevention and reduction of worker exposure to lead. These results suggest that the highest exposure occurred when no engineering or work practice controls were employed. Summary exposure levels under these conditions exceeded the Occupational Safety and Health Administration (OSHA) Permissible Exposure Level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 24 publications
0
19
0
1
Order By: Relevance
“…It has been suggested that lead loading is non-normally distributed, but BLL is normally distributed [16]. Summation of exposure data may be best represented as a geometric value (mean) [1,7]. that there is no relationship between the surface sampling methods, wipe and vacuum [21], if these proposed standards are applied the sampling method must be uniform and not interchanged.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been suggested that lead loading is non-normally distributed, but BLL is normally distributed [16]. Summation of exposure data may be best represented as a geometric value (mean) [1,7]. that there is no relationship between the surface sampling methods, wipe and vacuum [21], if these proposed standards are applied the sampling method must be uniform and not interchanged.…”
Section: Methodsmentioning
confidence: 99%
“…Lead abatement is developing into a separate environment industry in the United States [1][2][3][4][5][6]. This is a result of the risks associated with use of the heavy metal lead in building materials and subsequent regulations controlling exposure associated with building materials [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…permissible exposure limit -PEL), koja je za Singapur 0,15 mg/m 3 (150 µg/m 3 ) i veća je tri puta od one koju propisuje OSHA (50 µg/m 3 ). Pri analizi samo jednog uzorka, vrlo je verovatno da postoji velika varijacija date vrednosti, što zahteva ispitivanje većeg broja uzoraka [19].…”
Section: Diskusijaunclassified